Physicochemical composition and fatty acids profile of the meat of lambs fed with cassava wastewater - Urbano, Stela Antas; Ferreira, Marcelo Andrade; Azevedo, Paulo Sérgio; Vasconcelos, Gustavo Araújo; Santos Filho, Hilson Barreto; Cardoso, Daniel Barros (Federal University of Piauí, 2019)
The effects of replacing corn with cassava wastewater at 0; 25; 50; 75 and 100% in the sheep diet over chemical composition, fatty acid profile and physical-chemical parameters of meat were studied. Forty Santa Inês breed sheep were slaughtered after 70 days of confinement. The moisture content of meat increased, while the crude protein and ether extract decreased linearly with the replacement. There was a quadratic effect for shear force with minimum force estimated at 2.78 kg / cm ² with 54.25% replacement. There was a quadratic effect for C15:0 and C:17, (0.37 and 1.30 when the replacement was 46.25% and 68.50%, respectively), increasing linearly for the C18:0 and decreasing for the C22:0. For monounsaturated fatty acids there was a decreasing linear effect for C14:1 and C20:1 n9, and increasing to C18:1 n11. For C15:1 a quadratic effect was observed (1.48 when 26.75% of corn was replaced). As to the polyunsaturated fatty acids, there was a quadratic effect for C18:2 9c 11t (0.60 when replacement was 36.66%). There was a linear decrease for relations polyunsaturated: saturated and ω6: ω3, without effect on other relations. Cassava wastewater alters the shear force and chemical and lipid composition of meat.